OPTIMALISASI DANA ZAKAT DI INDONESIA (MODEL DISTRIBUSI ZAKAT BERBASIS PEMBERDAYAAN EKONOMI) - Amarudin, Muchamat (EKSYAR: Jurnal Ekonomi Syari'ah & Bisnis Islam, 2019)
Zakat has a social dimension to its own identity that can have a good impact on society, both as an effort to worship God and as an effort to care for fellow humans. However, zakat is not only limited to having this function. Optimizing the distribution of zakat funds in a professional manner will have a better impact on the distribution or income to the community. Meanwhile, up to now the distribution of zakat is considered to be not optimal. We can see that the distribution of zakat funds is limited to ordinary distribution and is only for consumption. Therefore, a more productive formulation of zakat funds is needed. The concept of distribution of zakat funds based on economic empowerment is the right answer, bearing in mind the potential of zakat funds can be the key to the existing social economic inequality in Indonesia.